Complementary and integrative practices inoral health: A Systematic Review - Filice de Barros, Nelson (Brazilian Dental Science, 2013)
Abstract Objective: To present a systematic literature review on the use of Complementary and Integrative Practices (CIP) in the field of dentistry. Methods: Randomized, controlled clinical trials (RCT) were selected from the PubMed-MEDLINE data base (2000-2010). The articles were classified according to the type of therapy, level of significance of results, impact factor and area of knowledge of the periodicals. Results: Ninety-one RCTs were included: 42(47%) are on Laser therapy, 32(35%) Phytotherapy, 14(15%) Acupuncture, 2(2%) Homeopathy and 1(1%) on Hypnosis. The results showed negative evidences, particularly for Laser therapy (n=28;31%), whereas Phytotherapy (n=20;22%), Acupuncture (n=11;12%) and Homeopathy (n=2;2%) presented higher frequency of positive results. The RCTs researched were published in journals related to dentistry (n=59;64%), medicine (n=21;23,5%), other areas (n=7;8%) and CIP (n=4;4,5%). Conclusions: It was concluded that there are positive evidences for the use of some types of CIP in oral health. However, they are limited as regards their quality and consistency, with little difference between the positive and negative results, characterizing little force of evidence, and consequently low potential for clinical application, in accordance with the principles of evidence-based dentistry. Keywords: Acupuncture; Homeopathy; Phytotherapy; Hypnosis; Flower Therapy; Laser Therapy.